MENCARI FILOSOFI DI DUNIA KONTEMPORER DAN DI LINGKUNGAN AKADEMIS: SEBUAH OPINI - Sukmayadi, Dodi (LPPM Universitas Terbuka, 2010)
This paper posits an opinion that the state of philosophy in contemporary world including in academic milieu is quiet unsatisfying in terms of how it is formulated and perceived. Though only lightly touched here and there, similar situation happens in Indonesia. Philosophy has been notoriously accused of corrupting young generations, of continuously irritating establishments, or at best leaves the world unchanged. Con-sidering that even music, for example, which satisfies only a few human sense, could have such enormous effect to human life, philosophy which claims to cover all traces of human existence could basically do something much much more, rather than simply uninfluencial or harming humanity. By elucidating initial and a little further meaning of philosophy, this paper try to build a foundation for such claim. In between such elucidation, it is briefly mentioned certain reasons why philosophy has been, is and will exist as long as human being exist. All in all, however, this article is only a beginning or at least the first part to explain the existensial nature of philosophy. A further article is needed to expound that.